Investigating the Mediating Role of Regulatory Focus between Career Commitment, Career Management and Career Satisfaction - Dr. Ahmad Tisman Pasha; Dr. Muhammad Shaukat Malik; Hira Muneer (Journal of Management Practices, Humanities and Social Sciences, 2022)
The goal of this research project is to investigate the impact that regulatory focus, specifically promotion focus and prevention focus plays in bridging the gap between career commitment, career management, and career satisfaction among permanent workers working in the insurance industry in Pakistan. A survey approach was used to gather data from 380 workers working in the insurance business, and random sampling was used to choose those employees. In order to evaluate the data, SPSS and the PLS-SEM approach were used. The findings of this research reveal that career satisfaction is positively related to career commitment and career management, as well as the influence of regulatory focus on these connections. Regulatory focus often refers to an individual's capacity to foresee and satisfy goals and eligibility criteria that have a major impact on career commitment and career management, that is advantageous and important for insurance industry personnel to achieve career satisfaction. In earlier research, the influence of regulatory focus on career commitment and career management connection with career satisfaction has been examined separately, but never in the context of the insurance industry in Pakistan.